2014
DOI: 10.1017/jfm.2013.666
|View full text |Cite
|
Sign up to set email alerts
|

Linearized oscillations of a vortex column: the singular eigenfunctions

Abstract: Lord Kelvin analysed the linearized inviscid oscillations of a Rankine vortex as part of a theory of vortex atoms. These eponymously named neutrally stable modes are, however, exceptional regular oscillations that make up the discrete spectrum of the Rankine vortex. In this paper, we examine the singular oscillations that make up the continuous spectrum (CS) and span the entire base state range of frequencies. In two dimensions, the CS eigenfunctions have a twin-vortex-sheet structure similar to that known fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 81 publications
1
15
0
Order By: Relevance
“…The spectrum is seen to borrow its traits from two constituent casesthe Rayleigh-Plateau configuration involving only surface tension (figure 1a) and the Rankine vortex involving only rotation (figure 1b). Much like the Rankine vortex, the rotating liquid column supports an infinite sequence of primarily Coriolis-force-driven modes (henceforth referred to as the Coriolis modes), with the inner dispersion curves corresponding to perturbations with an increasingly fine-scaled radial structure; note that the Rankine vortex has recently been shown to also possess a continuous spectrum on account of the irrotational shear in the column exterior (Roy & Subramanian 2014;Roy et al 2021). The Coriolis modes in both these problems have frequencies σ r ∈ (−2, 2).…”
Section: Axisymmetric Perturbationsmentioning
confidence: 99%
“…The spectrum is seen to borrow its traits from two constituent casesthe Rayleigh-Plateau configuration involving only surface tension (figure 1a) and the Rankine vortex involving only rotation (figure 1b). Much like the Rankine vortex, the rotating liquid column supports an infinite sequence of primarily Coriolis-force-driven modes (henceforth referred to as the Coriolis modes), with the inner dispersion curves corresponding to perturbations with an increasingly fine-scaled radial structure; note that the Rankine vortex has recently been shown to also possess a continuous spectrum on account of the irrotational shear in the column exterior (Roy & Subramanian 2014;Roy et al 2021). The Coriolis modes in both these problems have frequencies σ r ∈ (−2, 2).…”
Section: Axisymmetric Perturbationsmentioning
confidence: 99%
“…To the best of our knowledge no analytic expression of the resolvent for three-dimensional inhomogeneous perturbations about smooth viscous vortices exists today (e.g. Ash & Khorrami 1995, p. 321; Roy & Subramanian 2014, p. 439). However, it can be shown that normality of a linear operator implies normality of its resolvent (Kato 1980, pp.…”
Section: Selective Non-normality Of Linear Vortex Dynamicsmentioning
confidence: 99%
“…(Different from Antkowiak 2005, stating that combination of discrete and (unbounded) continuous spectrum.) Roy & Subramanian (2014, p. 405) demonstrate how the inclusion of singular modes pertaining to the inviscid continuous spectrum enables interaction between vortex and free stream, suggesting that a linear model of receptivity to ambient turbulence is intimately related to the inviscid continuous spectrum.…”
Section: Robustness Of Linear Vortex Receptivitymentioning
confidence: 99%
See 1 more Smart Citation
“…In a celebrated paper [18], Lord Kelvin considered the particular case of Rankine's vortex and proved that the linearized operator has a countable family of eigenvalues on the imaginary axis. The corresponding eigenfunctions, which are now referred to as Kelvin's vibration modes, have been extensively studied in the literature, also for more general vortex profiles [8,13,17]. An important contribution was made by Lord Rayleigh in [15], who gave a simple condition for spectral stability with respect to axisymmetric perturbations.…”
Section: Introductionmentioning
confidence: 99%